1991
DOI: 10.2105/ajph.81.10.1252
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic distribution of gonorrhea incidence: implications for prevention and behavioral research.

Abstract: BACKGROUND. Despite a declining incidence during the AIDS era, gonorrhea remains the most frequently reported communicable disease in the United States. METHODS. During 1986 and 1987 we supplemented gonorrhea case reporting with laboratory surveillance in King County, Washington. Incidence rates were correlated with demographic variables. RESULTS. Overall incidence of gonorrhea was similar for men and women, but highest for 16- to 21-year-old females and urban Seattle residents. Incidence rates by ethnicity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 8 publications
4
41
3
Order By: Relevance
“…26 Moreover, spatial distance between partners in core gonorrhoea areas is shorter than those in non-core zones. 13 Barlow et al showed a similar high level of assortative mixing in heterosexual patients attending a large London GUM clinic when the country of birth of the parents of the index patients is taken into account. 28 The geoclustering of chlamydia in our study, though somewhat less than that observed for gonorrhoea was remarkable.…”
Section: Figure 1 Prevalence Of Infection By Chlamydia Trachomatis (Lmentioning
confidence: 87%
“…26 Moreover, spatial distance between partners in core gonorrhoea areas is shorter than those in non-core zones. 13 Barlow et al showed a similar high level of assortative mixing in heterosexual patients attending a large London GUM clinic when the country of birth of the parents of the index patients is taken into account. 28 The geoclustering of chlamydia in our study, though somewhat less than that observed for gonorrhoea was remarkable.…”
Section: Figure 1 Prevalence Of Infection By Chlamydia Trachomatis (Lmentioning
confidence: 87%
“…While we were unable to determine if this association was truly contextual, and we did not find any support for the hypotheses that neighborhood joblessness and the ratio of men to women play important roles in determining sexual network position in this sample, our results suggest that the well-documented association between poverty and STI rates may operate through sexual network structure. [1][2][3][4][5][6]8 Further study of this possible mechanism should attempt to confirm these results in a larger sample, distinguish between contextual and compositional effects, and further elucidate how neighborhood socioeconomic environment may shape network structure. …”
Section: Discussionmentioning
confidence: 99%
“…This variation has been found to be strongly associated with various features of the socioeconomic environment, including income, unemployment, and education, [1][2][3][4][5] family structure, 6,7 community physical disorder, 1 racial/ethnic composition, 3,4,7 social capital, 5,8 racial/ethnic income inequalities, 6 and racial/ethnic residential segregation. 6 In particular, poor neighborhoods with high proportions of African American residents suffer from disproportionately high sexually transmitted infection (STI) rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] However, STIs are not uniformly distributed in the population, demonstrated amply in geographic analyses of STI incidence, which have shown different incidence rates in different subpopulations, with the highest rates occurring in poor, inner-city, densely populated, contiguous census tracts. [9][10][11][12][13] Therefore, cataloging risk behavior and demographic and socioeconomic characteristics has not provided adequate descriptions of STI risk. 11,[14][15][16] A more convincing explanation has been the hypothesis developed mathematically by disease ecologists that a small proportion of the population (core groups) who have high rates of STI and partner changes contribute disproportionately to STI transmission.…”
Section: Introductionmentioning
confidence: 99%